TIME CALCULATION METHODS OF THE BUGIS MAKASSAR TRIBE BASED ON THE KU TIKA BOOK - Sartika, Sartika (Fakultas Syari'ah dan Hukum UIN Walisongo, 2023)
The Bugis Makassar Tribe Society is one of the tribes in Indonesia that has historical traces in the calendar system. The method of calculating people's time in ancient times was contained in the Ku Tika manuscript of the Bone Tribe which until now is no longer used and is only used as a historical source. Many of today's generations do not know and are no longer able to be read by various backgrounds in society in general. This is because the language used in the text is not the same as today's language, such as the Lontara Bugis language. Therefore, a study is needed regarding the contents of the manuscript so that it can be known by all audiences. This research is included in library research, namely research by collecting data and information from books, journals, and other document records. Based on the results of the research, it can be seen that the Ku Tika manuscript of the Bone tribe explains the meaning of hours, days and months. The time calculation method used is called Pakkita Esso which means the system of five times in one day.